Validating Connection Amid Public Expenditure on Education, Health and Economic Growth in South - Adekunle, Ahmed (Acta Universitatis Danubius. Œconomica, 2023)
The aim of this study is to measure the impact of public expenditure and human capital on economic growth in South Africa. The data cover the period between 2000 and 2020. Through the VAR estimation model that is more appropriate to the structure of our data, the results reveal that Domestic general government health expenditure had a negative influence on economic growth in the second period but a positive impact in the first and third periods. GEED has consistently had a favorable and substantial effect on economic expansion. Experience has a detrimental effect on the second period and a good one on the first and third. Imp has a comparable effect on economic growth to exports, contributing favorably to growth in the first and third periods and adversely to growth in the second. In view of these results, economic policies must support the administration of human capital expenditures towards investment expenditures in the education and health sector.